Interação sócio-verbal: promoção da saúde de idosos residentes em instituição de longa permanência - Souza, Isis Aline Lourenço de (2014)
Brazil has been experiencing an exponential expansion of human longevity. The expressive increase in the elderly population alongside the situation of poverty in which a significant portion of Brazilian families live, incurs in a growing demand for long-stay institutions for the elderly. Thus, a preponderant fact in these institutions, which commonly represent social isolation for residents and aid in biological care, is the ineffective relationship held by the elderly residents among each other, leading them to inactivity and depression. This study aims to evaluate the impact of linguistic-discursive activities in health promotion in a group of elderly residents in a long-stay institution, located in a city in the south-central region in the country side of the state of Paraná, Brazil. This is a qualitative study, and the development of activities was guided by the focus group strategy, grounded in a dialogical perspective of language. Furthermore, in order to collect data, a semi-structured interview was applied to the elderly who composed the focus group. For the analysis and data interpretation, the Bakhtinian perspective of language was applied. Such statements show that an indispensable component to the promotion and maintenance of general health among institutionalized elderly is the language/interaction regarded as social work, meant to translate life in its different cycles. In this sense, the positive impacts related to the increase of socio-verbal activities in the life quality of the institutionalized elderly have been revealed by the strengthening of interpersonal relationships, by sharing experiences, by the use of language to release tension, by the engagement in a group activity, by the feasibility of production and knowledge exchange, by the establishment of mutual trust. Thus, the study highlights the focus group as a significant strategy for the development of language practice, indicating that socio-verbal activities, mediated by a phonoaudiologist grounded in a dialogical perspective, can be configured as an alternative capable of promoting health and (re) mean life of the elderly residents, empowering them as well as recovering their roles as human beings.